2018
DOI: 10.1016/j.socscimed.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

A safe haven for the injured? Urban trauma care at the intersection of healthcare, law enforcement, and race

Abstract: Patients with traumatic injuries often interact with police before and during hospitalization, particularly when their injuries are due to violence. People of color are at highest risk for violent injuries and have the poorest outcomes after injury. The purpose of this study was to describe how injured, Black patients perceived their interactions with police and what these perceptions reveal about police involvement within trauma care systems. We combined data from two qualitative studies to achieve this aim. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
(54 reference statements)
1
34
0
Order By: Relevance
“…All groups agreed that speed of transport was an advantage but identified different trade-offs and implementation challenges. Consistent with our prior research, patients reported pain and a sense of risk during police transport, 23 and were concerned that their injuries might have been worsened by transport in a vehicle not designed for injury care and stability. These concerns could be addressed by a combination of improved padding and safety restraints in police cars, by officers discussing these risks and benefits with patients in the moment, and by public education.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…All groups agreed that speed of transport was an advantage but identified different trade-offs and implementation challenges. Consistent with our prior research, patients reported pain and a sense of risk during police transport, 23 and were concerned that their injuries might have been worsened by transport in a vehicle not designed for injury care and stability. These concerns could be addressed by a combination of improved padding and safety restraints in police cars, by officers discussing these risks and benefits with patients in the moment, and by public education.…”
Section: Discussionsupporting
confidence: 76%
“… 19–22 Qualitative evidence has illustrated how some injured Black men associate police transport and their interactions with law enforcement prior to reaching a trauma center with additional pain and feelings of dehumanization. 23 24 Police transport may also pose underappreciated hazards to officers who provide injury first response with minimal medical training and equipment. Lastly, no studies have assessed variations in police transport and access to trauma care across a municipality or the effect on trauma care processes at a receiving center.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 27 , 28 In some cases, injured Black individuals transported by police report appreciating the improved scene safety and expedited hospital transport facilitated by responding officers. 29 Moreover, police transport may help diffuse scene anxiety and allay panic by responding to bystander requests for immediate assistance. 7 , 30 Police transport programs thus have the potential to change established negative perceptions of law enforcement by demonstrating altruistic attributes of the police in their neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study of traumatically injured black patients in Philadelphia, some who had experienced police hospital transport offered their view of the police role. They interpreted the speed and reassurances that officers provided en route as evidence that police were acting in service of their well-being (Jacoby et al 2017). Ongoing research in Philadelphia has similarly highlighted this perception.…”
Section: Is Police Hospital Transport Effective?mentioning
confidence: 99%